Poetry and translation - Robinson, Peter (Liverpool University Press, 2010)
Includes bibliographical references (pages 177-188) and index; This book examines the activity of translation as practised by poets and others, and how the various practices of translating have continued in parallel with the writing of original poetry. It seeks to raise issues and matters for discussion - the character of bilingual editions and how they are, or may be, read - not to close them down. The aim of the book is to increase knowledge of, and thought about, the interactive processes of reading and writing poetry composed in mother tongues and in translations; On first looking -- What is lost? -- Thou art translated -- The art of the impossible -- Nostalgia for world culture -- Translating the 'foreign' -- The quick and the dead